2008
DOI: 10.1179/174313408x353864
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Hepatosplenic Sarcoidosis by Contrast-Enhanced Ultrasound Guided Needle Biopsy

Abstract: Sarcoidosis is a systemic disease characterised by non-caseating multiple granulomas involving virtually any organ in the body. The aetiology and natural history of sarcoidosis remains obscure. Hepatosplenic sarcoidosis is rare with image-based diagnosis difficult if no other organ is already involved. This case report describes a patient with asymptomatic liver and spleen involvement in which a final diagnosis was achieved with contrast enhanced ultrasound (CEUS) guided liver biopsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…The spleen is particularly suitable for CEUS studies because of its location, small size, homogeneous parenchyma, rich vascularization, and intense and long‐lasting contrast enhancement 1–13. Several reports have shown that CEUS of the spleen significantly improves the diagnosis of parenchymal lacerations by enhancing the detection of avascular areas during the late phase of the examination 9–11.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The spleen is particularly suitable for CEUS studies because of its location, small size, homogeneous parenchyma, rich vascularization, and intense and long‐lasting contrast enhancement 1–13. Several reports have shown that CEUS of the spleen significantly improves the diagnosis of parenchymal lacerations by enhancing the detection of avascular areas during the late phase of the examination 9–11.…”
Section: Discussionmentioning
confidence: 99%
“…The splenic lymphoma appeared as a constantly hypoechoic lesion, more easily defined during the late phase but without clear intralesional microcirculation or rim enhancement in the early phase. Our findings indicated that a persistent hypoenhancing pattern of nodular splenic lesions may also be seen in benign lesions such as small abscesses or granulomas, so that differentiation of these lesions from malignant diseases is often not possible 8. To date, however, there have been no studies comparing CEUS with CT in the assessment of focal lesions of the spleen.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations